De novo variants in the PABP domain of PABPC1 lead to developmental delay - Wegler, Meret; Jia, Xiangbin; Alders, Marielle; Bouman, Arjan; Chen, Jia; Duan, Xinyu; Lauzon, Julie L.; Mathijssen, Inge B.; Sticht, Heinrich; Syrbe, Steffen; Tan, Senwei; Guo, Hui; et al. (Genetics in Medicine, 2022)
Purpose: The study aimed to investigate the role of PABPC1 in developmental delay (DD). Methods: Children were examined by geneticists and pediatricians. Variants were identified using exome sequencing and standard downstream bioinformatics pipelines. We performed in silico molecular modeling and coimmunoprecipitation to test if the variants affect the interaction between PABPC1 and PAIP2. We performed in utero electroporation of mouse embryo brains to enlighten the function of PABPC1. Results: We describe 4 probands with an overlapping phenotype of DD, expressive speech delay, and autistic features and heterozygous de novo variants that cluster in the PABP domain of PABPC1. Further symptoms were seizures and behavioral disorders. Molecular modeling predicted that the variants are pathogenic and would lead to decreased binding affinity to messenger RNA metabolism-related proteins, such as PAIP2. Coimmunoprecipitation confirmed this because it showed a significant weakening of the interaction between mutant PABPC1 and PAIP2. Electroporation of mouse embryo brains showed that Pabpc1 knockdown decreases the proliferation of neural progenitor cells. Wild-type Pabpc1 could rescue this disturbance, whereas 3 of the 4 variants did not. Conclusion: Pathogenic variants in the PABP domain lead to DD, possibly because of interference with the translation initiation and subsequently an impaired neurogenesis in cortical development.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Epilepsy; Exome; Intellectual disability; Neural progenitor cells; Neurodevelopmental disorder